AUTHORITATIVE PARENTING AND THE DEVELOPMENT OF PRE-SCHOOL AGE CHILDREN AT AL-AMIN KINDERGARTEN, MOJOROTO KEDIRI - dewi retno; Dewi Retno Puspitosari; M.Khoirudin - (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Preschool is an important period in a child's development. In reality, not all children can go through their growth and development period optimally because they experience disturbances in the growth and development process and various other factors. Parental parenting styles in child development really help children achieve and undergo normal growth and development according to their age level. This research aims to determine the relationship between parenting patterns and the development of preschool children at Al Amin Kindergarten Mojoroto Kediri. This research uses a cross sectional approach. Sampling used a total sampling technique with a total sample of 48 respondents (parents and children). The data collection technique was carried out by distributing parenting style questionnaires and observing the child's development. The data results were processed using univariate and bivariate analysis (Chi-Square). The research results showed that 43 (89.6%) mothers implemented a democratic parenting style and 21 (43.8%) children had development appropriate to their age. Based on the results of data processing, there is a relationship between parenting patterns and the development of preschool children at Al Amin Kindergarten Mojoroto Kediri (p-value 0.013). Based on this research, teachers are expected to carry out regular development assessments every year and provide education to parents about how to apply parenting styles and how to stimulate children's development so that activities to stimulate children's growth and development can be carried out in a coordinated manner in the form of a partnership between teachers and parents